Legal Review of Small and Medium Enterprises Who Choose Not to Scale Up Their Business - Canryfay Elisabet Lumban Gaol; Martono Anggusti; Meli Hertati Gultom (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the role of law for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia who choose not to scale up their businesses. This phenomenon is an important issue because this decision can have various consequences for MSMEs, including limited opportunities for expansion and competitiveness in an increasingly competitive market. Business scale-up itself is a strategy for developing small businesses so that they can grow larger in work capacity and competitiveness. The reluctance of MSMEs to increase their business scale is influenced by several factors, such as understanding the law, applicable regulations, and challenges in development related to the economic potential and contribution of MSMEs to national GDP. The research method uses a normative legal approach through literature studies and case approaches. The results of the study show that although MSMEs play an important role in supporting the Indonesian economy, many business actors feel comfortable with the current conditions and are reluctant to take risks to develop. Factors of apathy, limited human resources, and lack of technology adoption are the main obstacles to increasing business scale. The government has made various efforts, including through Law Number 20 of 2008 and Law Number 6 of 2023, to support the development of MSMEs. However, the implementation of these policies still faces challenges in the effectiveness of implementation at the regional and national levels. This study recommends strengthening synergies between the government, business actors, and the private sector in an effort to increase the competitiveness of MSMEs in a sustainable manner.